Effectiveness of Problem-Based Instruction Learning Methods on Adolescent Behavior in Preventing Covid-19 Transmission - Heri Triwibowo; Heni Frilasari; M. Sajidin (Kirana Publisher (KNPub), 2023)
Teenagers (students) still need to be given learning using the Problem-Based Instruction (PBI) method, because PBI can increase students' knowledge and creativity in critical thinking. This study aims to determine the effectiveness of the Problem-Based Instruction (PBI) learning method on adolescent behaviour in preventing the transmission of COVID-19 at SMPN 1 Mojoanyar Kab. Mojokerto. This study used a quasi-experimental design with a control group. The Sampling technique uses Total Sampling as many as 26 respondents. The researcher gave the stages in this study starting from collecting data by giving questionnaires to the treatment group and the control group. The treatment group was given an intervention using the Problem-Based Instruction (PBI) method which was carried out by giving a case which was then discussed together. This treatment was carried out 2 times within 1 week with various cases. Then a final assessment was carried out by filling out a questionnaire and followed by data analysis and drawing conclusions about the effectiveness of the Problem-Based Instruction (PBI) learning method on behaviour in the prevention of COVID-19 in both the treatment group and the control group. The results showed that the Problem-Based Instruction method was able to increase the behaviour of respondents in preventing the transmission of Covid-19, namely from 9 (34.6%) to 22 (84.6%). Meanwhile, in the control group, the number increased from 11 (42.3%) to only 12 (53.8%). The statistical test results show p-value = 0.000 less than = 0.05 so it can be concluded that H1 is accepted, which means that there is an influence of the Problem-Based Instruction learning method on changes in adolescent behaviour in preventing the transmission of COVID-19.